The relationships between economic motives and green IT adoption intention in Malaysia. - Abdul Jalil, Hartini; Nor Azam, Noor Haty; Yahya, Nur Fauzana; Md Deros, Mohd Nor; Abdul Razak, Nur Filzah (International Journal of Accounting, Finance and Business, 2024)
Empirical research on information systems (IS) is now crucial in determining the conditions that will encourage the uptake of green technology. Nonetheless, the majority of published IS research on green IT or green IS focuses on definitions, actions, and educational objectives. Furthermore, under the 2020 Malaysian Public Sector ICT Strategic Plan, green IT has emerged as a national agenda item and is currently serving as a strategy enabler in Malaysia. Still, there is a lack of knowledge on the significance of green IT practices. Thus, the purpose of this study is to investigate the impact of economic factors on the desire to adopt green IT in Malaysian public institutions. Such an endeavor is essential because green IT is a new field and only a tiny number of organizations large firms with significant financial backing, mostly have specific environmental management system certifications, as MS 14001 in Malaysia. The study used a positivist approach to investigate the roles of economic motives by surveying the topic and using public organizations as the respondents. According to the SEM-PLS, there is evidence that eco-efficiency, eco-effectiveness, eco-process, and eco-brand all predict the intention of adopting green IT. The results might be used to create a framework and paradigm for green IT adoption that would protect the environment from needless e-waste. Therefore, by using these insights, policy makers, stakeholders, and government agencies may be able to set better green technology uses benchmarking throughout a range of sectors.